Pattern Of Tinea Capitis In A Hospital-based Clinic In Alkhobar, Saudi Arabia - Aldayel Maha; Bukhari Iqbal (Wolters Kluwer Medknow Publications, 2004)
Tinea capitis is a dermatophyte infection of the scalp the purpose of this study was to define the demographic features, clinical patterns and associated symptoms and signs of tinea capitis in Saudi Arabia. All patients who attended the dermatology clinic of king Fahad Hospital of the University (KFHU) at Al-Khobar, Saudi Arabia and who were diagnosed as tinea capitis between January 1991 and December 2001 were reviewed. The collected data were analyzed using statistical package for social sciences (SPSS). A p value of less than 0.05 was considered as the statistical level of significance. The patients with tinea capitis composed 0.14% of the study population and male to female ratio was 1.8:1. The mean age at presentation was 6.4 + 5.2 years. The most frequent sign was alopecia and the predominant morphological type was the non inflammatory tinea capitis. Micorporum canis was the predominant dermatophyte followed by Trichophyton violaceum.